Fiscal Visibility in Spain: Two Types of Estimates - Miguel Roig-Alonso (European Regional Science Association (ERSA), 2004)
The size and pattern of any public budget depend, among other factors, on the visibility of both the burdens and the benefits of public revenue and public expenditure. Furthermore, such visibility is a necessary - not a sufficient - condition for an efficient allocation of resources between the private and public sectors of an economy. The aim of this contribution, based on a recent research, is to simultaneously present additive and arithmetic indicators for local, intermediate and central territorial government levels and to initially apply them to Spain by using data and information provided by the International Monetary Fund. Conclusions and comments are offered for general criticism, discussion, theoretical development and future application to other OECD countries.
Keywords: 330